Gut microbiome as a potential biomarker of cancer risk in inflammatory bowel disease - Jones, Ryan (Contemporary Oncology/Współczesna Onkologia, 2022)
Inflammatory bowel disease (IBD), a term used for Crohn’s disease and ulcerative colitis that are characterized by chronic inflammation of the gastrointestinal tract, has been suggested to be closely related to high risk of developing colorectal or gastric cancer [1]. Focusing on patient cases and studies, this study aims to identify the cause of a possible correlation between IBD and cancerous cells, and determine the influence of IBD on cancerous cells in patients. A gut microbiome analysis was utilized to understand the mechanisms of the disease and to find associations with it in patients. I analyzed the experimental data obtained through amplicon sequencing to target regions of interest, and determined genes associated with the correlation by using coding programs. Biological processes, which are regulated by many means including the control of gene expression, were shown to be increased in patients with IBD compared to healthy subjects. Two datasets were used, with one going over an amplicon sequence analysis of fecal samples from healthy subjects and patients diagnosed with ulcerative colitis or Crohn’s disease. I performed gut metagenome analysis on the data of the patients’ fecal samples. This along with taxonomy analysis allows me to see percentages of certain bacterium in the gut and find a link. I was able to determine that the patients with IBD had a higher percentage of dark matter and a higher guanine to cytosine content (GC-content) percentage. This huge difference in the amount of dark matter and GC-content in an individual’s human gut metagenome could be an indicator of someone potentially developing a disease.